Voices from India’s borderlands: indigeneity and the de-centering of dissent against the Citizenship (Amendment) Act (CAA) - Ahmed, Shaheen Salma (Nidān, 2020)
India’s Northeast region (NER) has been framed politically over the years in myriad ways, often as a frontier for resource extraction, or a frontier with strategic boundaries. It has also been perceived as the margins of a pan-Indian civilization, wherein the communities are constructed as the racial ‘other’. This construction has prevailed in even the precolonial discourse of difference when Assam was ruled by several dynasties and was a not part of the Mughal map. Colonialism accentuated these polarities through its administrative and ethnographic discourses. Despite being fairly integrated as a part of British India, postcolonial northeast India witnessed growing marginalisation from the centre. Issues of demographic change, resource extraction, governance, sovereignty remained political issues for movements from the region. The region remained as a ‘law and order’ situation for India. The delegitimization of voices from the Northeast has been a long historical process. The movements against CAA and the entanglements of NRC bring back those issues of ‘othering’ and ‘silencing’. ,